The Influence of Oil Price on Renewable Energy Stock Prices: an Analysis for Entrepreneurs - Vrînceanu, Georgiana; Horobeț, Alexandra; Popescu, Consuela; Belaşcu, Lucian (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
This study investigates the relationship between oil price fluctuations and renewable energy stock returns using daily data on Brent crude oil prices and global renewable energy stock market indices between 29 November 2010 and 18 February 2020. The investigation is based on the existing evidence on positive correlations between stock prices and oil prices, but it also considers the shift from non-renewable to renewable sources of energy. A two-stage GARCH(1,1) model and a Granger causality test were applied. Our results show that volatility clustering is present in the renewable energy companies‘ stock prices, but, oil price volatility does not seem to induce any significant effects on returns‘ volatility. This might suggest that oil markets and renewable energy markets are rather disconnected, which means that the development of renewable energy businesses is less affected by potential shocks in the oil prices and markets. As a result, the exposure of companies and entrepreneurs in the renewable sector to an important source of macroeconomic volatility is reduced.